PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PAKET INTERNET XL AXIATA DI MASA PANDEMI COVID 19: Indonesia - Sherwin Ary Busman; Gunawan Wibisono (Journal of Management and Business, 2021)
This study aims to analyze the effect of price and product quality on purchasing decisions for XL Axiata Internet Packages during the COVID-19 Pandemic on students of the Faculty of Economics and Business, University of Technology, Sumbawa. The research method used is quantitative with an associative approach. The sampling technique used non-probability sampling with a total of 90 respondents. The data collection technique used a questionnaire which was processed using SPSS. Data analysis used multiple linear regression. The results showed that price had a partial effect on purchasing decisions for XL Axiata internet packages during the COVID-19 pandemic and product quality had a significant effect on purchasing decisions for XL Axiata internet packages during the Covid-19 pandemic.